Analysis of Differences in Shibori Motif Results Using Rust Dyeing Technique on Cellulose Fibers and Synthetic Fibers - Kurniati Kurniati; Irmayanti Irmayanti; St. Aisyah St. Aisyah (Universitas Negeri Semarang, 2025)
Rust Dyeing is a dyeing technique that utilizes iron corrosion to create unique patterns with rust stains, producing colors ranging from yellow to black. The striking and long-lasting rust color makes it an attractive alternative for dyeing fabrics, with the color results influenced by the type of textile fiber. This study aims to: (1) Determine the differences in shibori pattern results in terms of color evenness, color sharpness, and clarity of the pattern, and (2) find the best rust dyeing technique on cellulose and synthetic fibers using the shibori technique. This comparative study uses the type of fiber as the independent variable (cellulose and synthetic) and shibori pattern results as the dependent variable (color evenness, color sharpness, and clarity of pattern). Data were collected from 8 observers and analyzed using ANOVA with SPSS 22 at a significance level of 5%. The results showed differences in shibori pattern results between cellulose and synthetic fibers. The best results were obtained on synthetic fabrics, especially satin fabrics, with the best mean in terms of color evenness (3.62), color sharpness (3.87), and clarity of pattern shape (3.87). The satin fabric produces even colors, clear and bright patterns, and sharp pattern.